2021
DOI: 10.1088/1755-1315/672/1/012072
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and gelatinization properties of ethanol-treated sorghum flour

Abstract: Granular cold-water swelling starch can be produced by ethanol-treated method. This work aims to determine the chemical, physical and gelatinization properties of ethanol-treated sorghum flour. White sorghum flour was heated in ethanol solution (45, 50 and 55 %v/v) with ratio of 1:9 at three temperature levels (60, 80 and 100 °C). The modified flour properties including moisture content, ash content, whiteness degree, and gelatinization properties were determined. The results showed that ethanol concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
2
0
0
Order By: Relevance
“…As shown in Tabel 3, the setback of sorghum ETF were decreased as heating temperature was increased. These results are in line with Yulianti et al [20] that increased in heating temperature causes a decrease in the setback viscosity of a white sorghum ETF. According to Zhu&Liu [19] the higher setback value, the easier to formed a gel.…”
Section: Gelatinization Profile Of Sorghum Floursupporting
confidence: 92%
See 1 more Smart Citation
“…As shown in Tabel 3, the setback of sorghum ETF were decreased as heating temperature was increased. These results are in line with Yulianti et al [20] that increased in heating temperature causes a decrease in the setback viscosity of a white sorghum ETF. According to Zhu&Liu [19] the higher setback value, the easier to formed a gel.…”
Section: Gelatinization Profile Of Sorghum Floursupporting
confidence: 92%
“…Based on Table 3, the final viscosity decreased with increasing heating temperature. Similar result were reported by Yulianti et al [20] that increase in heating temperature causes a decrease of final viscosity in a white sorghum ETF. Kurakake et al [21] also reported the same result that the swelling power and solubility of maize starch was decreased with increasing treatment temperatures.…”
Section: Gelatinization Profile Of Sorghum Floursupporting
confidence: 90%